2020
DOI: 10.1021/acs.molpharmaceut.0c00692
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Toxicity, Lung Distribution, and Cellular Uptake of Rifampicin and Ascorbic Acid-Loaded Alginate Nanoparticles as Therapeutic Treatment of Lung Intracellular Infections

Abstract: Nanotechnology is a very promising technological tool to combat health problems associated with the loss of effectiveness of currently used antibiotics. Previously, we developed a formulation consisting of a chitosan and tween 80-decorated alginate nanocarrier that encapsulates rifampicin and the antioxidant ascorbic acid (RIF/ ASC), intended for the treatment of respiratory intracellular infections. Here, we investigated the effects of RIF/ASC-loaded NPs on the respiratory mucus and the pulmonary surfactant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Nevertheless, a limited number of studies have been performed to confirm the safety of PLGA NPs in the short and long term, especially in the lung compartment [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a limited number of studies have been performed to confirm the safety of PLGA NPs in the short and long term, especially in the lung compartment [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies not focused on overcoming the lung biological barrier, for example alveolar macrophage targeting therapies, are not considered in the scope of this review. 49 2.2.1. Core material.…”
Section: Nm Engineering For Lung Mucus Penetrationmentioning
confidence: 99%
“…Therefore, CS modification has good potential for application in local mucosal drug delivery. Scolari et al [35] have reported functionalized alginate nanoparticles loaded with rifampicin (RIF) and the antioxidant ascorbic acid (ASC) with CS and the nonionic surfactant T80, thus providing a hydrophilic protective layer through the "sugar cluster effect" (Figure 2a). Experimental data have shown that nanoparticles loaded with RIF/ASC are mucus inert and can penetrate the mucus layer of the respiratory tract (Figure 2b) and become internalized.…”
Section: Chitosanmentioning
confidence: 99%